2014
DOI: 10.1177/0003489414554944
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Inflammatory Protein-1 Production and Eosinophil Infiltration in Chronic Rhinosinusitis With Nasal Polyps

Abstract: MIP-1α may play a role in eosinophil recruitment in NP. Our results suggest that the measurement of MIP-1α in nasal secretions could be useful in evaluating the degree of eosinophil inflammation and severity of disease in nonallergic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
12
1
1
Order By: Relevance
“…41 Eosinophil infiltration in CRSwNP involves a number of chemokines. 42 In our study, there was no correlation between ␣-defensins and blood eosinophil levels in all the groups, but a strong positive correlation was observed between NS ␣-defensins and NS IL-5 levels in the CRSwNP group. Eosinophils can constitutively express ␣-defensins and release them after activation, 43 which led us to hypothesize that the highest levels of ␣-defensins in CRSwNP may be contributed by eosinophilic granulocytes.…”
Section: Discussioncontrasting
confidence: 60%
“…41 Eosinophil infiltration in CRSwNP involves a number of chemokines. 42 In our study, there was no correlation between ␣-defensins and blood eosinophil levels in all the groups, but a strong positive correlation was observed between NS ␣-defensins and NS IL-5 levels in the CRSwNP group. Eosinophils can constitutively express ␣-defensins and release them after activation, 43 which led us to hypothesize that the highest levels of ␣-defensins in CRSwNP may be contributed by eosinophilic granulocytes.…”
Section: Discussioncontrasting
confidence: 60%
“…It has been shown that contents of nasal fluid reflect the inflammatory status of the nasal mucosa and parallel the evolution of mucosal disease . Our previous study demonstrated that chemokine levels in nasal secretions correlate well with clinical parameters and cytological findings in patients with chronic polypous rhinosinusitis . Cytological exploration of the nasal mucosa is a helpful path to better knowledge of pathophysiology of chronic inflammatory diseases and in correct differential diagnosis …”
Section: Discussionmentioning
confidence: 96%
“…8 MIP-1β is a chemokine for CCR5-expressing cells, including natural killer cells, monocytes, and eosinophils, and may participate in the prolongation of chronic inflammation in CRS. 9 The strengths and limitations of our current study are discussed in Data S1.…”
Section: A Panel Of Clinical and Biological Markers Predict Difficultmentioning
confidence: 99%